The effect of business environment on firm performance Exploratory Study: Case of Tunisian enterprises (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The objective of this paper is to identify the different framework characterizing the business environment and assess their impact on companies performance in order to identify the most dimension environmental affecting companies performance; new created as well as developed companies. Three mains categories of the business environment are suggested: socio-cultural, institutional and technological environment. To achieve this goal, our research is based on a literature review on the question followed by an empirical study on a sample of 96 companies to make the association between theory and reality An empirical study provides that the institutional and the technological factors are the most positively and significantly related to performance. Regarding the socio-cultural environment has a less significance on companies performance.